2021
DOI: 10.1126/sciadv.abd1239
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study in almost 195,000 individuals identifies 50 previously unidentified genetic loci for eye color

Abstract: Human eye color is highly heritable, but its genetic architecture is not yet fully understood. We report the results of the largest genome-wide association study for eye color to date, involving up to 192,986 European participants from 10 populations. We identify 124 independent associations arising from 61 discrete genomic regions, including 50 previously unidentified. We find evidence for genes involved in melanin pigmentation, but we also find associations with genes involved in iris morphology and structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 94 publications
0
46
1
Order By: Relevance
“…(37). However, the ILRUN locus identified in the present study was not amongst their novel signals, nor we were able to replicate it.…”
contrasting
confidence: 57%
See 3 more Smart Citations
“…(37). However, the ILRUN locus identified in the present study was not amongst their novel signals, nor we were able to replicate it.…”
contrasting
confidence: 57%
“…In our sample we have identified significant differences in self-reporting of eye colour between sexes, and although these may be a reflection of true sex differences, as has been previously reported in other studies reporting self-assessed categorical eye colour (9), we cannot discard the possibility of a self-reporting bias. This limitation is counter-balanced by the relatively large sample size, in comparison to the majority of previous studies (16,51,52), with the exception of the largest recent GWAS of eye colour (37). Furthermore, significantly associated loci from self-reported eye colour are useful in forensics, for predicting eye colour categories, which the human eye can easily distinguish.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Nevertheless, genomic analyses in previously understudied populations-like sub-Saharan African groups-suggest that perhaps hundreds of skin pigmentation alleles of small effect remain to be found (Martin et al, 2017b). Similarly, recent studies have shown that eye pigmentation is far more polygenic than previous thought (Simcoe et al, 2021). Recent quantitative and molecular genomic studies are painting an increasingly complex picture of the architecture of these traits, featuring more considerable roles for epistasis, pleiotropy and small-effect variants than were previously assumed (for an extensive review of skin pigmentation, see Quillen et al, 2019).…”
Section: Ancient Dna and Complex Trait Genomicsmentioning
confidence: 97%